The Effect of Hydrotherapy Exercise on Pain Intensity and Functional Ability in Genu Osteoarthritis Patients - Alda Trie Amelia; Nyimas Fatimah; Margareta Dewi Dwiwulandari (HM Publisher, 2020)
Background: Genu osteoarthritis (OA) is the most common arthritis disease caused by a degenerative joint process that causes knee pain and functional disorders. One of the recommended therapies for the treatment of OA genu from several studies is hydrotherapy exercises. Hydrotherapy exercises can reduce pain and improve the patient's quality of life. This study aims to determine the effect of hydrotherapy exercises on pain intensity and functional ability in OA genu patients. Methods: This study is a quasi-experimental study with a one-group pretest-posttest design conducted by the Medical Rehabilitation Installation of dr. Mohammad Hoesin Palembang during the month of October-November 2019. Primary data was collected using interviews to assess pain intensity based on the Numerical Paon Rating Scale (NPRS) score and functional ability based on the WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) questionnaire before and after training. hydrotherapy for 4 weeks for one therapy a week. The data was carried out by the Shapiro-Wilk normality test, then analyzed using the paired T-test or Wilcoxon test using the SPSS tool. Results: In as many as 31 study subjects, the results showed that there was a significant effect before and after hydrotherapy exercises on reducing pain intensity (p = 0.000) and improving functional ability (p = 0.000) in patients with OA genu for 4 weeks. Conclusion: There is an effect of hydrotherapy exercise on pain intensity and functional ability in genu osteoarthritis (OA) patients.